Implementation of coral triangle initiative on coral reefs, fisheries, and food security (CTI-CFF) in Indonesia and Philippines. Issue 1 (October 2020) - Anugrah, A P; Putra, B A; Burhanuddin,
Abstract: This study aims to discover and examine forms of implementation of the multilateral cooperation initiated by Indonesia in 2007 and agreed upon by five other nations located inside the Coral Triangle region in 2009 which was known as Coral Triangle Initiative on Coral Reefs, Fisheries, and Food Security (CTI-CFF) to safeguard the coral reefs and marine ecosystem inside the Coral Triangle region, to ensure sustainable fisheries practices and the achievement of food security in two of its members, Indonesia and Philippines. To achieve said objective, this study will exemplify the general situation in the Coral Triangle region, the circumstances being faced by Indonesia and Philippines in regard of their marine sector as a whole, and both legal proceedings and any supportive activities in relation to CTI-CFF that have been done in since its inception in 2009 by both nations. The result of this study indicates that the implementation of CTI-CFF inside the two countries was being based on a synthesis between recommendations inside CTI-CFF's Regional Plan of Action (RPoA). The document serves as a policy and regulation blueprint in both countries, being used in the making of regulations and policies in regard to fisheries management, food security, and marine ecosystem conservation. The influence of RPoA is apparent in many regulations, policies, and activities inside both countries, in which some explicitly contain the very recommendations contained inside the RPoA document.